La eficacia de los programas educativos en la reinserción social del adulto infractor - Lalangui Infante, Kenya Tatiana (2021)
The study maintains the objective of analyzing the legal status of access to an education given in detention centers and its incidence in the social reintegration phase of postconvicts, knowing in a preliminary way that there are weaknesses in the prison system that restrict the access to education, especially due to poor infrastructure. To delve into the subject, a qualitative approach methodology is applied by interviewing key informants, in addition to the quantitative approach through surveys of lawyers, collecting information that is complemented by the findings of the documentary research, especially the normative analysis…………